Le elezioni amministrative del 13 ottobre 2019 in Ungheria. Il Fidesz vince nella provincia ma perde Budapest: è sfida aperta per le politiche del 2022 (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
On October 13, local elections were held in Hungary and the political outcome is mixed. Fidesz strengthens its consensus throughout the nation, however, opposition parties celebrate a stunning victory in Budapest and in many other cities. Opposition parties united behind a single candidate in almost every riding in order to defeat Fidesz candidates. Prime Minister Viktor Orbán is called upon not to ignore the message the voters have sent. The local elections were a test of the opposition’s political competitiveness before the 2022 general elections. Despite Viktor Orbán’s landslide victories in the 2018 Hungarian and 2019 European elections, a future win is not a given. Fidesz is no longer invincible.